Long-tailed macaques: an unfairness model for humans. Issue 1 (31st December 2022) - Agung Nugroho, Dwi Atmoko; Sajuthi, Dondin; Supraptini Mansjoer, Sri; Iskandar, Entang; Shalahudin Darusman, Huda
ABSTRACT: The current study was designed to predict why human primates often behave unfairly (equity aversion) by not exhibiting equity preference (the ability to equally distribute outcomes 1:1 among participants). Parallel to humans, besides inequity aversion, lab monkeys such as kin of long-tailed macaques (Macaca fascicularis) also demonstrate equity aversion depending on their preference for the outcome (food) type. During the pre-experiment phase, a food-preference test was conducted to determine the most preferred income per individual monkey. Red grapes were the most preferred outcome (100%) when compared to vanilla wafers (0%). The first set of experiments used a 1:1 ratio (equity condition) of grape distribution among six kin-pairs of female long-tailed macaques, and we compared their aversion (Av) versus acceptance (Ac). In the second experiment, we assessed the response to the 0:2 and 1:3 ratio distribution of grapes (inequity condition). A total of 60 trials were conducted for each condition with N = 6 pairs. Our results show aversion to the inequity conditions (1:3 ratios) in long-tailed macaques was not significantly different from aversion to the equity conditions (1:1 ratios). We suggest that the aversion observed in this species was associated with the degree of preference for the outcome (food type) offered rather than the distribution ratio. The subjective preferences for outcome types could bring this species into irrationality; they failed to share foods with an equal ratio of 1:1.